(3JdNjU cJGH eLeY GdBOGH GdeQJH Ydi eYLe GdCSeGA aj eYLe GdCdbGHs - (3YHO GdQGRb Hf CMeO GdahWj GdTjHGfj,J (B723 (3g` s
(3ChdgG (B:s
(3jHOC eef dbHg YR GdOjf s
(3BNQgG (B:s
(3jfJgi Edi ef dbHg bhGe GdOjf s
(3GdfSNI HgG MhGTs
(3hGdejcQhajde Hg Jda HSjWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B202 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B43 s
Keywords: (3GdJGQjNs